2000
DOI: 10.1080/02571862.2000.10634877
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × environment interaction of winter wheat (Triticum aestivum L.) in South Africa: I. AMMI analysis of yield performance

Abstract: Thirteen winter and intermediate type bread wheat cultivars were evaluated under dryland conditions over a four year period from 1991 to 1994 and over 120 environments in the Free State province of South Africa. The Additive Main Effects and Multiplicative Interaction (AMMI) statistical model was used to describe genotype-environment (G x E) interaction of yield performance under dryland conditions. In all three relatively homogeneous production regions, viz. Western, Central and Eastern Free State, the AMMI m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 11 publications
(10 reference statements)
1
37
0
1
Order By: Relevance
“…The materials comprised of seventeen genotypes G 1 (NIAW 1885) The AMMI stability value (ASV) described by Purchase et al (2000a) was calculated as follows: AMMI Stability Value (ASV)= Where, SSIPCA1/SSIPCA2 is the weight given to the IPCA1 value. The higher the IPCA score, either negative or positive, the more specifically adapted a genotype is to certain environments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials comprised of seventeen genotypes G 1 (NIAW 1885) The AMMI stability value (ASV) described by Purchase et al (2000a) was calculated as follows: AMMI Stability Value (ASV)= Where, SSIPCA1/SSIPCA2 is the weight given to the IPCA1 value. The higher the IPCA score, either negative or positive, the more specifically adapted a genotype is to certain environments.…”
Section: Methodsmentioning
confidence: 99%
“…The meaningful interpretation of data to support a breeding program such as genotype stability is necessary at multi locations trials ISSN : 0974-9411 (Print), 2231-5209 (Online) All Rights Reserved © Applied and Natural Science Foundation www.ansfoundation.org (Gauch and Zobel 1996). The AMMI model has been used extensively in recent past to analyze and interpret genotype × environment interactions and results can be displayed graphically (Crossa et al, 1990;Purchase et al, 2000a). The Indian wheat programme coordinated by the Indian Institute of Wheat and Barley Research, Karnal, Haryana.…”
Section: Introductionmentioning
confidence: 99%
“…To further explain the GEI and adaptation an additional biplot between the IPCA 1 scores and IPCA 2 scores were performed and yield stability was determined by using the AMMI stability value (ASV) as described by Purchase (1997). AMMI Stability Value (ASV) = This stability value was reported to be a balanced measurement between the two IPCA scores (Purchase, 1997). In effect the ASV is the deviation from zero in a two dimensional scattergram of IPCA 1 scores against IPCA 2 scores.…”
Section: Methodsmentioning
confidence: 99%
“…Crossa (1990) and Ebdon and Gauch (2002) reported that the combined analysis of variance and principle components analysis in the AMMI model, along with the predictable assessment, is a valuable approach for understanding GEI through which better yield estimates are obtained. Use of AMMI analysis is recommended by a number of scientists (Smith & Smith, 1992;Steyn et al, 1993;Yau, 1995;Purchase, 1997;Abamu, et al, 1998;Purchase, et al, 2000a;2000b;Ebdon & Gauch, 2002;Hugh & Gauch, 2006) for detailed studies of GEI, especially when data sets are large, as in national or international trials.…”
Section: Introductionmentioning
confidence: 99%
“…モデル (Bradu andGabriel 1978, Gauch 1988, Gauch and Zobel 1988)では,いくつかの安定性指標値が提唱され, 品種における形質の安定性評価に用いられている (Zhang et al 1998a, 1998b, Purchase et al 2000, Li et al, 2006, Farshadfar 2008, Farshadfar et al 2011) .また,遺伝子型の 効果を調整し, 主成分分析の可視化手段であるバイプロッ トの理解が容易な GGE バイプロットモデル (Gabriel 1971, Yan andKang 2003)は,よく用いられている手法で ある.これらの手法は,収量形質の安定性評価のために 考案され,用いられてきたが (Crossa 1990, 1991, Yan and Kang 2003) ,現在まで広範な農業形質 への応用例が報告されている (Zhang et al 2003, 八城ら 2004,Mohammadi et al 2011, Thangavel et al 2011 …”
unclassified